Laccase wiring on free-standing electrospun carbon nanofibres using a mediator plug. Issue 78 (7th October 2015) - Bourourou, M.; Holzinger, M.; Elouarzaki, K.; Le Goff, A.; Bossard, F.; Rossignol, C.; Djurado, E.; Martin, V.; Curtil, D.; Chaussy, D.; Maaref, A.; Cosnier, S.
<x xml:space="preserve">Abstract</x> The enzyme laccase was wired on a free-standing electrospun carbon fiber mat using a cross-linker plug based on the pyrene modified electron shuttle ABTS.